How Work Stress Intermediate Work-Family Conflict And Workload To Employee Performance? - Frendy Ilham Saputra; Suhendra Suhendra (Enrichment : Journal of Management, 2022)
This research aims to test the impact of Work-Family Conflict and Workload on Employee Performance through Variable Intervening Work Stress. The data used in this study are primary and secondary. In this study, the analytical method used is path analysis and the Sobel test. The number of respondents was 84, which was determined by the non-probability and purposive sampling techniques. The results of this study indicate that in the structural path analysis equation 1, there is (1) work-family conflict there is no significant direct effect on work stress, (2) workload has a significant effect on work stress, (3) work-family conflict and workload have an effect significant to work stress. The structural path analysis equation 2 shows that (4) work-family conflict has a significant effect on employee performance, (5) workload has no direct and significant effect on employee performance, (6) work stress has a significant effect on employee performance, 7) work stress as a mediating variable has no significant effect between work-family conflict on performance, (8) work-family conflict, workload, and work stress have a significant effect on employee performance, (9) work stress as a mediating variable has a significant influence between workload on employee performance.